Islamic Educational Values in the Asy-Syuro Tradition: A Case Study of Bumi Rahayu Village - Bima Wisnu Gunawan; Dedi Setiawan; M. Saidun Anwar (Assyfa Journal of Islamic Studies, 2026)
This study aims to examine and analyze the Islamic educational values contained in the Asy-Syuro tradition in Bumi Rahayu Village, Bumi Ratu Nuban District, Central Lampung Regency. The Asy-Syuro tradition is a religious-cultural practice carried out every night of the 1st of Muharram and has become an integral part of the local community's life. This tradition not only functions as a religious ritual but also serves as a medium for internalizing Islamic educational values that are passed down from generation to generation. This research employs a qualitative approach using an ethnographic method, aiming to understand the meanings and values contained in the traditional practices from the community's perspective. Data collection techniques include observation, in-depth interviews, and documentation. The research informants consist of religious leaders, community leaders, and residents of Bumi Rahayu Village who are directly involved in the implementation of the tradition. The data obtained were analyzed descriptively through the processes of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the Asy-Syuro tradition contains three main values of Islamic education: aqidah (faith), ibadah (worship), and akhlak (morality). The value of aqidah is reflected in strengthening faith through collective prayers, dhikr, and the recitation of Surah Yasin. The value of ibadah is seen in the implementation of religious rituals performed congregationally with solemnity. Meanwhile, the value of akhlak is manifested in attitudes of togetherness, mutual cooperation, social care, and the tradition of sharing through takiran. In addition, this tradition functions as an effective non-formal Islamic educational medium in shaping the religious and social character of the community across generations. Thus, the Asy-Syuro tradition can be understood as a form of integration between local culture and Islamic teachings, serving as a medium for education based on local wisdom.